Penerapan Model Pembelajaran Make A Match Untuk Meningkatkan Motivasi Belajar Di SMPN 30 Makassar - Mappeasse, Nurul Zazkiyah; Mustamin, Mustamin; Abdullah, Nuraeni; Raehana, Syarifa; Syahrul, Muhammad (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study is the effectiveness of the “Make a Match” learning model in Islamic Religious Education learning for class VIII.9 at SMPN 30 Makassar and its impact on students’ learning motivation. Classroom Action Research (CAR) was implemented by involving 30 students (17 males and 13 females) as research subjects. Data collection instruments consisted of observation sheets and learning motivation questionnaires consisting of 16 statement items. The results showed a significant increase in students’ learning motivation after the implementation of the “Make a Match” model. The average score of the questionnaire in cycle II (1449 points, equivalent to 75.46%) increased compared to cycle I (1213 points, equivalent to 63.17%). This finding supports the hypothesis that the “Make a Match” model is effective in increasing students’ learning motivation in the context of Islamic Religious Education learning. This study recommends the use of interactive and interesting learning models to optimize students’ learning motivation.